2017
DOI: 10.3390/met7070245
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Surface Precipitates on Ultrafine-Grained Titanium in Physiological Solution

Abstract: Enhanced cell adherence to the surface of nanocrystallized commercially pure titanium (CP-Ti) was observed by several authors. However, the understanding of the surface modification of Ti in a physiological solution due to nanocrystallized grain size has not been reached. In this work, equal channel angular pressing (ECAP) was applied to manufacturing ultrafine grained CP-Ti. Martensite and Widmanstatten microstructures were also obtained for comparison. The CP-Ti pieces with different microstructures were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Since that time, many in vitro as well as in vivo studies have investigated the impact of nanostructured surfaces on the behavior of the surrounding cells [ 18 , 19 ]. Zhou et al [ 20 ] suggested one possible explanation, based on changes in the chemical composition of titanium surface immersed in a simulated body fluid (SBF) with an addition of bovine serum albumin (BSA). The higher levels of calcium, phosphorus and oxygen found on the surface of UFG titanium are beneficial to the bioactivity of the titanium implant [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, many in vitro as well as in vivo studies have investigated the impact of nanostructured surfaces on the behavior of the surrounding cells [ 18 , 19 ]. Zhou et al [ 20 ] suggested one possible explanation, based on changes in the chemical composition of titanium surface immersed in a simulated body fluid (SBF) with an addition of bovine serum albumin (BSA). The higher levels of calcium, phosphorus and oxygen found on the surface of UFG titanium are beneficial to the bioactivity of the titanium implant [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A combination of a single ECAP pass followed by cold rolling exhibited a good compromise between mechanical properties and processing efforts, which emphasizes application potential for precursors to UFG microstructures. Zhou et al [2] demonstrated spontaneous modification of the surface of titanium with different substrate microstructures after soaking in a physiological solution. In this research, commercial purity (CP) titanium was processed by ECAP to achieve UFG microstructure and was immersed in simulated body fluid for 60 days.…”
Section: Contributionsmentioning
confidence: 99%
“…For instance, implants with smaller load-bearing cross-sections are suitable for children [6]. In terms of biocompatibility, pure titanium is associated with increased osteoblast proliferation and better osseointegration [6,7]. Kim and Park [7] established a model explaining enhanced surface cell attachment on nanocrystallized commercially pure titanium (CP–Ti).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of biocompatibility, pure titanium is associated with increased osteoblast proliferation and better osseointegration [6,7]. Kim and Park [7] established a model explaining enhanced surface cell attachment on nanocrystallized commercially pure titanium (CP–Ti). The reason for this is that the number of nodules at the triple-point junctions of the grain microstructure increases as the grain size is refined through equal-channel angular pressing (ECAP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation